Coupling stabilizers open K(V)1-type potassium channels - Silverå Ejneby, Malin (Proc Natl Acad Sci U S A, 2020)
The opening and closing of voltage-gated ion channels are regulated by voltage sensors coupled to a gate that controls the ion flux across the cellular membrane. Modulation of any part of gating constitutes an entry point for pharmacologically regulating channel function. Here, we report on the discovery of a large family of warfarin-like compounds that open the two voltage-gated type 1 potassium (K(V)1) channels K(V)1.5 and Shaker, but not the related K(V)2-, K(V)4-, or K(V)7-type channels. These negatively charged compounds bind in the open state to positively charged arginines and lysines between the intracellular ends of the voltage-sensor domains and the pore domain. This mechanism of action resembles that of endogenous channel-opening lipids and opens up an avenue for the development of ion-channel modulators.